Sosialisasi Internal di Perusahaan PT Borneo Samarinda Mengenai Perilaku dan Dampak Job Hopping - Rosyid Nurrohman; Diva Wulan Mentari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The phenomenon of job hopping has become an important concern in the dynamics of modern employment, especially among generations X, Y, and Z. Frequent job changes in a short period are often triggered by various factors, ranging from the pursuit of job satisfaction, the need for flexibility, to the desire to gain broader experience (Arlita & Sari, 2025). The internal socialization activities conducted at PT Borneo Samarinda aim to enhance employees’ understanding of job hopping behavior and its impact on organizational stability and company productivity. These activities are carried out in the form of interactive sharing sessions involving employees across divisions. The socialization materials include the understanding of the job hopping concept, main causes in each generation, negative impacts on the company, and adaptive solutions that can be implemented by management and employees. Results show increased participant awareness regarding the risks of job hopping, particularly related to reduced loyalty, high recruitment costs, and loss of institutional knowledge. Open discussions during the sessions revealed employees’ commitment to be more reflective about their personal careers and loyalty to the company. This socialization is expected to be a preventive step that encourages strengthening the organizational culture and creating a balance between individual satisfaction and corporate sustainability.